2020
DOI: 10.3390/math8071185
|View full text |Cite
|
Sign up to set email alerts
|

Baker–Campbell–Hausdorff–Dynkin Formula for the Lie Algebra of Rigid Body Displacements

Abstract: The paper proposes, for the first time, a closed form of the Baker–Campbell–Hausdorff–Dynkin (BCHD) formula in the particular case of the Lie algebra of rigid body displacements. For this purpose, the structure of the Lie group of the rigid body displacements S E ( 3 ) and the properties of its Lie algebra se ( 3 ) are used. In addition, a new solution to this problem in dual Lie algebra of dual vectors is delivered using the isomorphism between the Lie group S E ( 3 ) and the Lie group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…( 22), the symbol ⋄ denotes the composition operation for rotation parameters, whose explicit form depends on the respective rotation parameters. For LGIM, the composition operation for Euler angles is given in [11], for the rotation vector in, e.g., [11,34], and for Euler parameters in, e.g., [3,12].…”
Section: Rigid Body Kinematics On R 3 × So(3)mentioning
confidence: 99%
“…( 22), the symbol ⋄ denotes the composition operation for rotation parameters, whose explicit form depends on the respective rotation parameters. For LGIM, the composition operation for Euler angles is given in [11], for the rotation vector in, e.g., [11,34], and for Euler parameters in, e.g., [3,12].…”
Section: Rigid Body Kinematics On R 3 × So(3)mentioning
confidence: 99%
“…(e) The Jacobian J An important quantity in rotational geometry and kinematics is the (left) Jacobian J of SO(3), which relates angular velocity to the Euler axis-angle variables: ω = J φ. The Jacobian is furthermore related to the rotation matrix by C = 1 + φ × J = 1 + Jφ × and can be given explicitly as [17,33,34] royalsocietypublishing.org/journal/rspa Proc. R. Soc.…”
Section: (D) the Inverse Of Cmentioning
confidence: 99%
“…An important quantity in rotational geometry and kinematics is the (left) Jacobian J of SOfalse(3false), which relates angular velocity to the Euler axis-angle variables: bold-italicω=Jbold-italicϕ˙. The Jacobian is furthermore related to the rotation matrix by C=1+ϕ×J=1+Jϕ× and can be given explicitly as [17,33,34] J=k=0bold-italicϕ×kfalse(k+1false)!=1+1cosϕϕbolda×+ϕsinϕϕa×bolda×.But it can also be determined with the help of the foregoing eigendecomposition. Note that the Jacobian is equally obtained by [17,35] J=01boldCα dα.Using complex decomposition, …”
Section: Rotations—sofalse(3false)mentioning
confidence: 99%
“…for some a, b, and c such that the result is an element of SE(3). We know that higher-order powers of ξ ∧ are unnecessary owing to (13), which comes from the Cayley-Hamilton theorem.…”
Section: B Vector Mappings For Posesmentioning
confidence: 99%
“…For SE(3), Condurache and Ciureanu [18] recently discussed a closed-form solution for compounding two pose vectors in the case that φ = ϕa. Bauchau and Choi (2003) showed that we can easily generalize this result to any of our vectorial pose parameterizations.…”
Section: Compounding Posesmentioning
confidence: 99%